Case Report: Head injury presenting as lower cranial nerve palsy - Gupta, Shubham; Gupta, Rakesh; Sheikh, Zafar; Bele, Abhijeet (Frontiers in Surgery, 2025)
Lower cranial nerve palsy is a rare condition, most commonly caused by malignant skull base lesions or internal carotid artery dissection, and only rarely resulting from trauma. We report two cases of road traffic accident victims presenting with lower cranial nerve palsy involving cranial nerves IX, X, and XI. Both patients had similar clinical complaints. The most important findings were a dislocated occipital condyle fracture and suspected associated soft tissue injury. Both were treated conservatively with a rigid cervical collar. A nasogastric tube was required for the first patient during the initial recovery period due to severe dysphagia, while the second patient tolerated oral intake and did not require enteral feeding. Both patients showed gradual improvement in symptoms during hospitalization and follow-up. These injuries, with their often subtle clinical presentation, may be easily overlooked and require prompt detection to prevent complications.